2022
DOI: 10.1002/solr.202101087
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Energy Band Alignment and Mobile Ions on Interfacial Recombination in Perovskite Solar Cells

Abstract: A key limitation in perovskite solar cell (PSC) performance is suboptimal electronic properties at the perovskite–transport layer (TL) interfaces, which result in parasitic nonradiative recombination. Interface recombination depends on the concentration of recombination‐active defects, but as a recombination event requires both an electron and a hole, the magnitude and sign of charge accumulation at the perovskite–TL heterojunctions are also critical. Here, we employ a well‐established numerical ion‐electron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Several theoretical studies, including our own, have shown that altering the distribution of ionic charge, and concurrently the distribution of electrons and holes, can influence rates of non-radiative recombination, which ultimately explains many manifestations of hysteresis in PSCs. 13,15,20,21 In our theoretical exploration of the TCO's influence, we observed that the greater the influence of the TCO on the perovskite layer, the higher the rate of nonradiative recombination at any given defect density due to increased accumulation of minority charge carriers at the TL-TCO interface. This was consistent with our experimental observations in the substitution between TiO 2 and TiO x N y , 1 which showed an B8 mV increase in open circuit voltage.…”
Section: View Article Onlinementioning
confidence: 99%
“…Several theoretical studies, including our own, have shown that altering the distribution of ionic charge, and concurrently the distribution of electrons and holes, can influence rates of non-radiative recombination, which ultimately explains many manifestations of hysteresis in PSCs. 13,15,20,21 In our theoretical exploration of the TCO's influence, we observed that the greater the influence of the TCO on the perovskite layer, the higher the rate of nonradiative recombination at any given defect density due to increased accumulation of minority charge carriers at the TL-TCO interface. This was consistent with our experimental observations in the substitution between TiO 2 and TiO x N y , 1 which showed an B8 mV increase in open circuit voltage.…”
Section: View Article Onlinementioning
confidence: 99%
“…One of the most promising and environmentally friendly energy sources is electricity generated by solar cells. The organic-inorganic hybrid perovskite-based solar cells (PSC) show a promising future for photovoltaic technology [1]. During the last decade, the power conversion efficiency (PCE) of PSCs has grown from 3.8% to more than 25.7% [2], making them a very rapidly advancing technology and a popular topic in the field of solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the power conversion efficiency (PCE) of PSCs has grown from 3.8% to more than 25.7% [2], making them a very rapidly advancing technology and a popular topic in the field of solar cells. The high performance of PSCs can primarily be attributed to their excellent optoelectronic properties, such as (1) strong light absorption through the entire visible spectrum range, enabling the use of thin perovskite films [3,4]; (2) high carrier mobility [5,6]; (3) long carrier diffusion length [7,8]; (4) high defect tolerance [9]; and (5) long lifetime of the generated charge carriers [10,11]. To realize the good performance of a PSC, high-quality perovskite film containing a low density of defects must be employed in a single device [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskite solar cells (PSCs) are emerging as the most promising optoelectronic devices due to the extraordinary optoelectronic properties of perovskite materials, such as tunable bandgap, high absorption coefficient and carrier mobility, high defect tolerance, and long-range carrier diffusion length. [1][2][3][4][5][6] After distinguished efforts have been devoted to the aspects of crystalline engineering, [7,8] interface engineering, [9,10] and additive strategy, [11,12] the record power conversation efficiency (PCE) of PSCs has been reached up to 25.8%. [13] To further improve the photovoltaic performance of single-junction PSCs beyond the Shockley-Quiesser limit of 33%, tandem solar cells based on transparent PSCs have gradually emerged and achieved major advancements.…”
Section: Introductionmentioning
confidence: 99%